2017
DOI: 10.1111/eci.12743
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of incident obesity phenotype in nonobese healthy adults

Abstract: While baseline BMI and WC were detrimental for developing MHO vs. MUHO, gender was the strongest predictor of incident obesity phenotype in healthy nonobese individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Obesity is not a uniform condition [8,9,10]. Generally, obesity is categorized into four phenotypes according to metabolic and anthropometric status: metabolically unhealthy obesity (MUO), metabolically unhealthy normal weight, metabolically healthy obesity (MHO), and metabolically healthy normal weight (MHNW) [9]. Individuals with MHO have been shown to have a lower risk of CVD and mortality compared with those with MUO [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is not a uniform condition [8,9,10]. Generally, obesity is categorized into four phenotypes according to metabolic and anthropometric status: metabolically unhealthy obesity (MUO), metabolically unhealthy normal weight, metabolically healthy obesity (MHO), and metabolically healthy normal weight (MHNW) [9]. Individuals with MHO have been shown to have a lower risk of CVD and mortality compared with those with MUO [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The most common cause of metabolic syndrome has been presumed to be abdominal obesity [11]. In recent years, however, the need to consider nonobese metabolic syndrome has received attention [12]. Unlike obese metabolic syndrome, for which body weight reductions can decrease the risk and which has received much attention in health care, nonobese metabolic syndrome has no common cause, such as obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Eftekharzade et al 36 found that among all suggested predictors of metabolic outcome, female gender played the strongest role. Also, in our study all genes were significant only in women.…”
Section: Discussionmentioning
confidence: 99%